Islamic Philanthropy and Social Services in Improving Community Welfare in Indonesia - Makhrus, M; Hasan, Ibnu; Budi Santoso, Selamet Eko (Islamic Economics Journal, 2024)
Poverty in Indonesia has become a complex and multisectoral issue, necessitating comprehensive handling involving all stakeholders, including civil society and Islamic philanthropy managers. Islamic philanthropic activism in Indonesia continues to expand, as evidenced by a growing public understanding of the importance of channeling donations through institutions. Donations collected by Islamic philanthropic organizations are channeled into charity programs for non-urgent needs and productive programs with lasting effects on community empowerment. This form of research employs a qualitative-descriptive methodology. This study examines an Islamic philanthropic organization using documentation and observation techniques to collect data, and qualitative deductive and inductive methods to analyze the data qualitatively. The findings of this study indicate that Islamic philanthropy and social services in improving welfare carried out by Islamic philanthropy management organizations in Indonesia are manifested in various fields, including social, economic, educational, and health, and are channeled as assistance and empowerment programs to improve public welfare. The organization’s capacity to manage Islamic philanthropy is achieved by integrating its programs, policies, and services with government and private agencies with similar objectives. In measuring the impact of Islamic philanthropy and social services on enhancing community welfare, Islamic philanthropic organizations consider a change in thought patterns, attitudes, and actions in living life based on one’s abilities. Consequently, charitable social services have taken the form of empowerment programs in a society with lasting effects.